Reduction of exposure to blood donors in preterm infants submitted to red blood cell transfusions using pediatric satellite packs - Uezima,Cristina Lika (2013)
OBJECTIVE: In preterm newborn infants transfused with erythrocytes stored up to 28 days, to compare the reduction of blood donor exposure in two groups of infants classified according to birth weight. METHODS: A prospective study was conducted with preterm infants with birth weight <1000g (Group 1) and 1000-1499g (Group 2), born between April, 2008 and December, 2009. Neonates submitted to exchange transfusions, emergency erythrocyte transfusion, or those who died in the first 24 hours of life were excluded. Transfusions were indicated according to the local guideline using pediatric transfusion satellite bags. Demographic and clinical data, besides number of transfusions and donors were assessed. . Logistic regression analysis was performed to determine factors associated with multiple transfusions. RESULTS: 30 and 48 neonates were included in Groups 1 and 2, respectively. The percentage of newborns with more than one erythrocyte transfusion (90 versus 11%), the median number of transfusions (3 versus 1) and the median of blood donors (2 versus 1) were higher in Group 1 (p<0.001), compared to Group 2. Among those with multiple transfusions, 14 (82%) and one (50%) presented 50% reduction in the number of blood donors, respectively in Groups 1 and 2. Factors associated with multiple transfusions were: birth weight <1000g (OR 11.91; 95%CI 2.14-66.27) and presence of arterial umbilical catheter (OR 8.59; 95%CI 1.94-38.13), adjusted for confounders. CONCLUSIONS: The efficacy of pediatrics satellites bags on blood donor reduction was higher in preterm infants with birth weight <1000g.